Tugas dan Wewenang Badan Kepegawaian Pendidikan dan Pelatihan dalam Menjamin Netralitas ASN pada Pemilihan Kepala Daerah Kota Kupang 2024 - Jitro Seprianus Faot (Universitas Proklamasi 45, 2026)
This study analyzes the role of the Regional Civil Service, Education and Training Agency (BKPPD) of Kupang City in ensuring the neutrality of the State Civil Apparatus (ASN) during the 2024 Regional Head Election (Pilkada). The method used is an empirical juridical approach through case studies and interviews with relevant stakeholders. The findings show that BKPPD plays a crucial role in disseminating regulations, monitoring ASN activities, and handling violations of neutrality. Legal violations by ASN often include direct or indirect support for regional head candidates, which clearly contradicts Law No. 5 of 2014, Law No. 20 of 2023, and Government Regulation No. 94 of 2021 on Civil Servant Discipline. Legal sanctions that may be imposed include written warnings, moderate to severe disciplinary punishment, and even dismissal from office. Although the legal framework exists, challenges such as limited understanding of legal norms among ASN and political pressure from local actors remain significant obstacles. Law enforcement is often ineffective due to limited resources and weak reporting mechanisms. Therefore, a more operational legal foundation and continuous legal education are needed to raise ASN's legal awareness. Synergy between BKPPD, Bawaslu, and the Civil Service Commission (KASN) is also essential to strengthen oversight and sanctions. This study offers strategic recommendations to ensure that the principle of ASN neutrality is implemented consistently and in accordance with the rule of law.